Implementation of Project Based Learning Based on the Independent Curriculum in Preparation Learning for Fashion Making at Vocational Schools - Wulansari Prasetyaningtyas; Sri Endah Wahyuningsih; Dwi Putri Asih; Luluk Witanti; Bilqis Lailatul Mardliyah; Anindya Rahma Suwignyo (Jurnal Penelitian Pendidikan, 2026)
The implementation of the Independent Curriculum in Vocational High Schools (SMK) requires learning that is contextual and relevant to the characteristics of vocational education. Project Based Learning (PjBL) is recommended, but its implementation in vocational learning still faces various challenges. This study aims to describe the implementation of Project Based Learning based on the Independent Curriculum and an indication of its impact on students' competence in learning Phase F Fashion Making Preparation at SMK. This study uses a mixed methods approach with a sequential exploratory design involving 37 teachers and 120 students from three vocational schools in Semarang City. Data were collected through questionnaires, observations, interviews, as well as pre-test and post-test tests and analyzed descriptively. The results of the study show that the implementation of PjBL is still partial with variations in readiness between schools. Key challenges include limited practice facilities, authentic assessments, and learning time. The implementation of PjBL shows indications of improving student competence, as shown by an increase in knowledge scores from 62.4 to 81.7 and skill achievements in the good and excellent categories.